(untitled) (Bangladesh Journal of Nuclear Medicine, 2025)
Background: The association between type 2 diabetes mellitus (T2DM) and bone mineral density (BMD) remains unclear. Screening, identification and prevention of potential risk factors for osteoporosis in T2DM patients are important and necessary for preserving a good quality of life and decreasing the risk of fracture. This study is expected to help us find the trend of BMD in T2DM patients in Bangladesh and identify any risk factors that may predispose to low BMD. Objective: To evaluate the bone mineral density in patients with long term history of type-2 diabetes mellitus. Procedure: This cross sectional observational study was conducted in NINMAS for a period of 18 months among 200 patients with history of T2DM for more than five years who were referred for BMD test. The study subjects were divided according to duration of DM, glycemic status, BMI, menstrual status etc. DEXA scan was done and BMD was measured at lumbar (L1 to L4) vertebrae, right and left femoral necks. After getting the BMD report (normal, osteoporosis, osteopenia), the effects of independent variables (age, gender, duration of diabetes, status of diabetes and BMI) on dependent variable (BMD) were analyzed. Result: Most patients were older (>50-60 and >60-70 years age group), female (85%), overweight and pre-obese. Mean age was 57.86 ±9.69 years. Most of them (158) were post-menopausal. Only 25.5% patients had good controlled diabetes. According to duration, most patients (61%) belonged to >5-10 years group. No statistically significant difference was found between the T-scores of the ‘pre-menopausal’ and ‘post-menopausal’ female. Among the patients, 67.5% had low spine BMD and 38% and 41% had low right and left femoral neck BMD respectively. Duration of DM had statistically significant association on BMD only in left femoral neck (p= 0.046). No statistically significant correlation was found between HbA1c and T-score. Women have more than five times chance of having low BMD than men (odds ratio= 5.185, p = <0.001) in spine. Independent risk factors for low BMD were female gender, increasing age and low BMI. Conclusion: Significant portion of T2DM patients had low BMD. Low BMD in left femoral neck has statistically significant association with duration of T2DM. Low BMD is also related to increasing age, female gender and low BMI. Bangladesh J. Nuclear Med. 27(2): 260-266, 2024